A rare case report of ovarian torsion with sigmoid volvulus - Mevada, Shraddha A.; Bhosale, Archana A.; Mehendale, Madhuri A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian torsion results from twisting of the ovary about the suspensory ligament, which contains the ovarian artery and vein, lymphatic’s, and nerves. Volvulus is a torsion of a segment of the alimentary tract, that often leads to intestinal obstruction. Ovarian torsion leading to sigmoid volvulus is the rarest complication which authors found in this case. Hence the case was presented. A 28-year-old women presented with acute pain in abdomen since 14 hours, followed by 2 episodes of vomiting, abdominal distension since 10 hours. Plain X-ray Abdomen erect was done which showed ‘Coffee bean’ sign with multiple air fluid levels suggestive of sigmoid volvulus. On laparotomy, after opening the peritoneum, large right ovarian cyst around 12×11×10 cm with solid and haemorrhagic content with long pedicle around 8 cm with 3 turns of torsion was noted. Abutting the ovarian mass, sigmoid colon was seen twisted around its mesentery including the twisted ovarian pedicle. Hence, the twisted component included the twisted ovarian pedicle and twisted sigmoid mesentery. Stepwise detorsion of ovarian pedicle followed by oophorectomy was done. For sigmoid volvulus, resection of vascular compromised sigmoid colon and descending colon stoma was done. Reanastomosis was done later after 3 months post operatively.